Sleep Disturbance and Strain Among Caregivers of Persons Living With Dementia - Osakwe, Zainab Toteh; Senteio, Charles; Bubu, Omonigho Michael; Obioha, Chinedu; Turner, Arlener D.; Thawani, Sujata; Saint Fleur-Calixte, Rose; Jean-Louis, Girardin (Frontiers in Aging Neuroscience, 2022)
Objective. The study objective was to examine predictors of sleep disturbance and strain among caregivers of persons living with dementia (PLWD). Methods. This cross-sectional study utilized a sample of community-dwelling older adults and their family caregivers drawn from the 2017 National Health and Aging Trends Study and National Study of Caregiving. Multivariable logistic regression was used to assess the association between caregiver and PLWD characteristics and a composite measure of caregiving strain. High caregiving strain was defined as a total score of ≥ 5 on the 6 caregiving strain items (e.g., emotional difficulty, no time for self). We used multivariable proportional odds models to examine predictors of caregiver sleep-related outcomes (trouble falling back to sleep and interrupted sleep), after adjusting for other caregiver and PLWD factors. Results. Of the 1142 family caregivers, 65.2% were female, 15% were Black, and 14% were Hispanic. Average age was 60 years old. Female caregivers were more likely to report high level of strain compared to male caregivers (OR:2.61, 95% CI=1.56, 4.39). Compared to non-Hispanic Whites, non-Hispanic Black and Hispanic caregivers had reduced odds of reporting greater trouble falling back asleep (OR=0.55, CI [0.36, 0.82] and OR=0.56, CI [0.34, 0.91], respectively). The odds of reporting greater trouble falling back asleep was significantly greater among caregivers with high blood pressure versus caregivers without high blood pressure (OR=1.62, CI [1.12, 2.33]). Conclusion. In this cross-sectional study, caregivers with greater sleep difficulty (trouble falling back asleep) were more likely to report having high blood pressure. We found no racial/ethnic differences in interrupted sleep among caregivers to PLWD. These results suggest that interventions to improve sleep among caregivers to PLWD may decrease poor cardiovascular outcomes in this group.